Dental Treatment Abuse - PAUL CHALAKKAL (Journal of Clinical and Diagnostic Research, 2014)
These case reports highlight dental treatment abuse performed by a quack on children. The anterior teeth of these children were metal capped using cement, which were otherwise healthy. The treatment was done on children without parental consent by a quack from Denmark who gave the reason as for resolving proclination of upper permanent incisors. The unanatomic, unaesthetic metal caps were removed after the child reported to the Department of Pedodontics and Preventive Dentistry.